17q21 variant increases the risk of exacerbations in asthmatic children despite inhaled corticosteroids use. Issue 10 (9th July 2018) - Farzan, N.; Vijverberg, S. J.; Hernandez‐Pacheco, N.; Bel, E. H. D.; Berce, V.; Bønnelykke, K.; Bisgaard, H.; Burchard, E. G.; Canino, G.; Celedón, J. C.; Chew, F. T.; Chiang, W. C.; et al.
Abstract :